A Portrayed of Social Class In Korean Movie "Parasite" Directed By Bong Joon-ho - Ailsya Avriel Azzahra; Suchi Amalia M; Nazwa Baidillah; Yuli Rohmiyati; Ana Utami Fatoni (EDUJ : English Education Journal, 2024)
Literature is a work created in the form of imaginative fiction which is the existence can be useful for other things. This study explore how the film Parasite, directed by Using qualitative analysis, the research examines key scenes about disparities in areas like living conditions, food, clothing, and even smell, revealing the effects of economic inequality on everyday life and relationships. Bong Joon-ho, portrays social class differences through the lives of two families—the wealthy Parks and the struggling Kims. Through these scenes, Parasite shows the complexities of class structures and how they shape people’s perceptions and interactions. The study offers insights into how films like Parasite can help viewers understand social issues, contributing to educational discussions on class and society. This analysis, in turn, supports English education by using film as a way to explore and discuss themes of inequality, making it a valuable resource for understanding social dynamics in both academic and cultural situation.